Constructive Action Semantics for Core ML - Iversen, Jørgen; Mosses, Peter D. (BRICS Report Series, 2004)
Usually, the majority of language constructs found in a programming language can also be found in many other languages, because language design is based on reuse. This should be reflected in the way we give semantics to programming languages. It can be achieved by making a language description consist of a collection of modules, each defining a single language construct. The description of a single language construct should be language independent, so that it can be reused in other descriptions without any changes. We call a language description framework ``constructive'' when it supports independent description of individual constructs. We present a case study in constructive semantic description. The case study is a description of Core ML, consisting of a mapping from it to BAS (Basic Abstract Syntax) and action semantic descriptions of the individual BAS constructs. The latter are written in ASDF (Action Semantics Definition Formalism), a formalism specially designed for writing action semantic descriptions of single language constructs. Tool support is provided by the ASF+SDF Meta-Environment and by the Action Environment, which is a new extension of the ASF+SDF Meta-Environment.